Landfill Leachate: Review of various treatment approaches - Lokesh Sapkota,; Rajendra Joshi,; Anish Ghimire,; Lakisha Shrestha,; Sophie Shrees,; Bikash Adhikari, (Journal of Innovations in Engineering Education, 2023)
The burning issue of Solid waste management has become more prevalent in municipals of emerging nations as a combined effort of population growth, economic expansion, and rising living standards. In Nepal, 48.6% of municipalities choose to pile rubbish in landfills, while the remaining municipalities choose to burn their waste or pile it up along rivers. Leachate, a hazardous pollutant that harms soil, ground and surface water, human health, hygiene, and aquatic life, is a liquid produced from the bottom of solid waste disposal facilities.Leachate is treated via three processes: physical, chemical, and biological in landfills. The goal of the current paper is to review the leachate treatment options currently on the market. Instead of adopting a single treatment procedure, with physical and chemical process in combination of biological treatment has shown the effective performance. The onsite leachate solution is given an appropriate low cost option via land treatment of the landfill leachate. Cover soil can be thought of as a primary component of landfill operating strategy for separating trash from the environment and employed as a medium for the reduction of organic loads and specific toxic metals in leachate. This paper will be helpful in examining the many alternatives for treating landfill leachate.